Pengaruh Kesulitan Keuangan terhadap Likuiditas Bank yang Dimoderasi oleh Sentimen Investor - Sanditya, Norma; Marietza, Fenny (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine how investor sentiment factors influence the relationship between financial distress and bank liquidity. This research was conducted as a form of empirical gap in previous research, so this research was conducted to re-examine the effect of financial distress on bank liquidity by adding the investor sentiment factor as a moderating variable. The novelty in this research is the addition of the investor sentiment factor as a moderating variable which will strengthen the influence of financial distress on bank liquidity. The population in this study were banks listed on the Indonesia Stock Exchange (BEI) in 2019-2022 and the sample used was 37 banks with 148 observations. The data analysis method was carried out using multiple linear regression analysis with Moderation variables (MRA), with the help of Eviews software. The results of this study state that financial distress have no effect on bank liquidity and investor sentiment cannot strengthen or weaken the effect of financial distress on bank liquidity.